Estimating CO2 emissions from emergency-supply transport: The case of COVID-19 vaccine global air transport. (15th March 2022) - Sajid, Muhammad Jawad; Ali, Ghaffar; Santibanez Gonzalez, Ernesto D.R.
Abstract: The environmental cost of disaster-related emergency supplies is significant. However, little research has been conducted on the estimation of emergency-supply transportation-related carbon emissions. This study created an "emergency supply emission estimation methodology" (ESEEM). The CO2 emissions from the global air dispatch of COVID-19 vaccines were estimated using two hypothetical scenarios of one dose per capita and additional doses secured. The robustness of the model was tested with the Monte Carlo Simulation method (MCM) based one-sample t -test. The model was validated using the "Expression of Uncertainty in Measurement (GUM)" and GUM's MCM approaches. The results showed that to dispatch at least one dose of the COVID-19 vaccine to 7.8 billion people, nearly 8000 Boeing 747 flights will be needed, releasing approximately 8.1 ± 0.30 metric kilotons (kt) of CO2 . As countries secure additional doses, these figures will increase to 14, 912 flights and about 15 ± 0.48 kt of CO2 . According to the variance-based sensitivity analysis, the total number of doses (population), technology, and wealth play a significant role in determining CO2 emissions across nations. Thus, wealthy nations' long-term population reduction efforts, technological advancements, and mitigation efforts can benefit the environment as a whole and the CO2 burdens associated with current COVID-19 and any future disasters' emergency-supply transportation. Graphical abstract: Image 1 Highlights: We developed a new method to estimate disaster-related emergency supply emissions. We estimated the CO2 emissions from the COVID-19 vaccine's global air transport. We filled a gap in emergency-supplies environmental impact literature.